Experimental study on particle breakage of carbonate gravels under cyclic loadings through large-scale triaxial tests. (September 2021) - Cao, Zhigang; Chen, Jiaji; Ye, Xingchi; Gu, Chuan; Guo, Zhen; Cai, Yuanqiang
Abstract: Carbonate gravels are often used as a road base filling material in island area. To evaluate the feasibility of carbonate gravels as a filling material, a large-diameter cyclic triaxial testing system (LDCTTS) was adopted to investigate the particle breakage and long-term behavior of carbonate gravels under high-cycle loadings ( N  = 50000). The effects of cyclic deviatoric stress, initial static deviatoric stress, effective confining pressure and drainage conditions on the long-term behavior of carbonate gravels were investigated. Fractal theory and Einav's relative breakage index were applied for the analysis of particle breakage. Test results show that the accumulated axial strain of carbonate gravels increases with the increase of cyclic deviatoric stress and initial deviatoric stress. Particle breakage occurs during the cyclic loading tests, especially for coarse particles with diameter>10 mm. The relative breakage index increases linearly with the cyclic deviatoric stress and the initial deviatoric stress, while decreasing exponentially with the effective confining pressure for the stress range studied. In addition, carbonate gravels in undrained tests exhibit more crushing than drained tests due to the positive pore water pressures accumulated. Einav's relative breakage index is found to be in an exponential relationship with the input of plastic deformation energy, which can be used to predict the particle breakage of carbonate gravels under cyclic loadings.